2020
DOI: 10.1002/jia2.25550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low‐level viraemia on virological failure among Asian children with perinatally acquired HIV on first‐line combination antiretroviral treatment: a multicentre, retrospective cohort study

Abstract: Introduction The clinical relevance of low‐level viraemia (LLV) and virological outcomes among children living with HIV (CLHIV) remains controversial. This study aimed to determine the impact of LLV on virological failure (VF) among Asian CLHIV on first‐line combination antiretroviral therapy (cART). Methods CLHIV aged <18 years, who were on first‐line cART for ≥12 months, and had virological suppression (two consecutive plasma viral load [pVL] <50 copies/mL) were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In this review, the non-availability of biological parents as primary caregivers has been associated with an increased risk of VF [ 34 , 37 , 40 ]. This finding is in consonant with a multicenter retrospective cohort study in the Asian-Pacific [ 59 ]. Having family members other than biological parents/grandparents as primary caregivers increased the risk of subsequent VF among Asian children living with HIV.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this review, the non-availability of biological parents as primary caregivers has been associated with an increased risk of VF [ 34 , 37 , 40 ]. This finding is in consonant with a multicenter retrospective cohort study in the Asian-Pacific [ 59 ]. Having family members other than biological parents/grandparents as primary caregivers increased the risk of subsequent VF among Asian children living with HIV.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this review are at variance with what has been documented in studies in other developing countries outside the sub-Saharan region. In Thailand, Cambodia, and India, the mean VF ranged from 3.3 to 27% in children treated for HIV 1 using the WHO standard first-line ART for a period not less than six months [ 55 - 59 ]. This highlights a higher success rate in the management of HIV compared to rates obtained in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies reported the prevalence of VF, being 19.2% in South Africa (12), 25.5 in Cameroon (13), 64% in Senegal (14), 37% in Kenya (15), 23% in Asia (16), 29.2% in Iran (17), and 26% in the Netherlands (18). Cross-sectional studies conducted in resourcelimited countries have reported a risk of VF ranging from 11% to 66% (19)(20)(21), and a 3-year probability of VF in Ghana was found to be 31% (22).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported PLLV as an independent indicator of VF while others disagree, especially about the significance of low-level low-range viremia. Notably, clinical implications differ among patients with PLLV ≤ 199 copies/ml and patients with higher viremia 200-<1000 copies/ml, with the latter being associated with VF [ 4 , 5 , 8 11 ]. The increasing evidence on the negative impacts of PLLV, especially persistent VL between 20 and 999, has led some organizations in resource-rich settings (RRS) to adopt guidelines lowering the ≥1000-copies/ml threshold of VF set by WHO.…”
Section: Introductionmentioning
confidence: 99%